Surface-capped copper nanoadditive for improvement of base oil properties (Bangladesh Journal of Scientific and Industrial Research, 2019)
Copper nanoparticles surface-capped by alkanethiol with long carbon chain length was prepared successfully by chemical reduction method. 1-dodecanethiol was used as the coating material for the desired smooth and protected surface. Various reaction parameters, like effect of pH, molar ratio of the reactants etc. had been tested experimentally to explore the most suitable and economical way of using the chemical reduction method. Uniform, smooth surface and spherical shaped copper nanoparticles, with particle size of about 40-60 nm had been produced successfully. Copper nanoparticles surface-capped by alkanethiol (C12S-Cu) was characterized by means of x-ray diffraction, scanning electron microscopy, Fourier transform infrared spectrometry and ultraviolet-visible spectroscopy. Uniform dispersion of copper nanoadditive in base oil using ultrasonic method was investigated. The tribological behavior of C12S-Cu as an additive for base oil was evaluated. Viscosity, pour point, and flash point of nano lubricants at different concentrations of nanoadditive (0.2, and 0.5 wt %) were evaluated.Bangladesh J. Sci. Ind. Res.54(1), 1-10, 2019